MENINJAU KEMBALI GLASGOW COMA SCALE: MASIHKAH RELEVAN? - Arthur Hendrik Philips Mawuntu (PERDOSNI, 2019)
REVISITING THE GLASGOW COMA SCALE: IS IT STILL RELEVANT?ABSTRACTGlasgow Coma Scale (GCS) is the most popular quantitative assesment of consciousness. Its popularity is gained by the simplicity of the assessment making the scale easy to be performed by medical officers from various background. Glasgow Coma Scale was rapidly adopted worldwide since its first publication in 1974. The wide adoption of the scale has affected the improvement of head injury management as well as other neurological conditions. Furthermore, many large scale studies about head injury have used this scale to evaluate degree of severity and prognosis. After more than 40 years, GCS has underwent various critisms and modifications. The last modification was published on 2014. Some cutting edge devices and new evaluation methods have been introduced in the last two decades that, probably, reduced the role of GCS. However, GCS still seems to be relevant in evaluating patients’clinical condition periodically, therefore we need to understand the development of GCS, its relevance in the present, and some modification of GCS.Keywords: Glasgow Coma Scale, history, relevanceABSTRAKGlasgow Coma Scale (GCS) atau Skala Koma Glasgow (SKG) adalah metode penilaian kuantitatif kesadaran yang paling popular. Popularitasnya justru disebabkan oleh kesederhanaan metode penilaiannya, sehingga mudah dikerjakan oleh petugas kesehatan dari berbagai latar belakang. Glasgow Coma Scale diadopsi dengan cepat di seluruh dunia setelah dipublikasikan pertama kali pada tahun 1974. Hal ini berdampak secara luas pada perbaikan manajemen cedera kepala dan penyakit neurologis lain, serta berbagai penelitian. Setelah lebih dari 40 tahun, skala ini melewati berbagai kritik dan modifikasi, yaitu terakhir pada tahun 2014. Berbagai alat pemeriksaan canggih dan metode penilaian baru telah diperke- nalkan dalam dua dekade terakhir sehingga mungkin mengurangi peran GCS. Meskipun demikian, masih digunakan untuk mengevaluasi keadaan klinis pasien secara berkala, sehingga perlu diketahui tentang perjalanan GCS, relevansinya di masa kini, serta beberapa modifikasi SKG.Kata kunci: Relevansi, sejarah, Skala Koma Glasgow